The Potential of Astrocytes as Immune Modulators in Brain Tumors - Priego, Neibla; Valiente, Manuel (Frontiers in Immunology, 2019)
The neuro-immune axis has emerged as a key aspect to understand the normal function of the Central Nervous System (CNS) as well as the pathophysiology of many brain disorders. As such, it may represent a promising source for novel therapeutic targets. Glial cells, and in particular the extensively studied microglia, play important roles in brain disorders. Astrocytes, in their reactive state, have been shown to positively and negatively modulate the progression of multiple CNS disorders. These seemingly opposing effects, might stem from their underlying heterogeneity, an aspect that has recently come to light. In this article we will discuss the link between reactive astrocytes and the neuro-immune axis with a perspective on their potential importance in brain tumors. Based on the gained knowledge from studies in other CNS disorders, reactive astrocytes are undoubtfully emerging as key component of the neuro-immune axis, with ability to modulate both the innate and adaptive branches of the immune system. Lastly, we will discuss how we can exploit our improved understanding of the basic biology of astrocytes to further enhance the efficacy of emerging immune-based therapies in primary brain tumors and brain metastasis.